2022
DOI: 10.1007/s11077-022-09462-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation use and learning in public policy

Abstract: Scientific evidence has become increasingly important for the decision-making processes in contemporary democracies. On the one hand, research dealing with the utilization of scientific knowledge in the political process has pointed out that decision-makers learn from evidence to improve policies to solve problems. On the other, scholars have underlined that actors learn from evidence to support their political interests regardless of how it affects the policy problem. One conventional insight from the policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Numerous research studies, numbering in the hundreds, have concluded that evaluation results are either not used or underused. For instance, despite the creation of evaluation units within parliaments in recent decades, studies indicate that parliamentarians seldom utilize evaluation findings or lack the capacity to fully benefit from the information and analysis derived from evaluations (Bundi, 2023). "Evaluators can enhance the utility of evaluations when they pay attention to the parliamentarians' needs.…”
Section: Resolving the Problem Of Underutilizationmentioning
confidence: 99%
“…Numerous research studies, numbering in the hundreds, have concluded that evaluation results are either not used or underused. For instance, despite the creation of evaluation units within parliaments in recent decades, studies indicate that parliamentarians seldom utilize evaluation findings or lack the capacity to fully benefit from the information and analysis derived from evaluations (Bundi, 2023). "Evaluators can enhance the utility of evaluations when they pay attention to the parliamentarians' needs.…”
Section: Resolving the Problem Of Underutilizationmentioning
confidence: 99%
“…When the level of conflict is low, it is difficult to draw actors’ attention to the new information (see, for instance, Baumgartner et al, 2009). On the other hand, when the level of conflict is high, each side defends its original positions and does not wish to pay attention to new information (Bundi & Trein, 2022; Nohrstedt et al, 2017).…”
Section: Policy Learningmentioning
confidence: 99%
“…Our introduction to this Handbook will not further explore the challenges presented by Fischer's approach to policy evaluation, but rather highlight that evaluation is always a political activity (Eliadis et al, 2011;Weiss, 1975). Evaluators should be aware of the political forces shaping the evaluation scope and process, or their findings bear the risk of being instrumentalized to reinforce existing power relations (Bundi & Trein, 2022). This Handbook thus focuses on the political dimension of the policy evaluation process rather than the technical and methodological problems about how best to capture the net effects of a public policy.…”
Section: The Inherent Politics Of Policy Evaluationmentioning
confidence: 99%